Gabriel García Márquez and the Sentimental Narrative: Love, Demons and Sad Whores - Aparicio, Yannelys (2025)
In the last two decades of his narrative works, García Márquez wrote several novels whose main theme is love. He tried to accommodate the style, tone and treatment to the parameters of the romantic novel of the 19th century. El amor en los tiempos del cólera (1985) was the first of these, whose immediate model was Flaubert’s Sentimental Education (1869) and its close inspiration María (1867), the Colombian romantic novel par excellence. The author himself confessed that he wanted to “write a nineteenth-century novel, as it was written in the nineteenth century, as if it were written in the nineteenth century” (in Arroyo, 1985, p. 1). His next novel, El general en su laberinto (1989), focused not only on the life of the independence hero but also on his intense and extensive love life, in an equally romantic context, typical of the first decades of the 19th century. And his last two novels, Del amor y otros demonios (1994) and Memoria de mis putas tristes (2004), despite being set in the colonial period in the first and in the late twentieth century in the second, also used specific resources of nineteenth-century romanticism, corroborating the trend that Aníbal González has called “new sentimental narrative” in the decades following the Latin American boom.